Analysis of the Role of Law in Environmental Dispute Resolution: A Case Study in Urban Areas - Karina, Ica; Polii, Johanis L. S. S.; Putra, Irman; Lubis, Arief Fahmi; Miharja, Marjan (Jurnal Smart Hukum (JSH), 2025)
The objective of this research project is to conduct an in-depth examination of the role of law in environmental dispute resolution within the context of urban Yogyakarta. By employing a qualitative methodology, this study examines the factors affecting the implementation of environmental legislation and the efficacy of legal instruments in addressing disputes. This study seeks to elucidate the role of law in environmental dispute resolution in Yogyakarta, examine the obstacles and impediments encountered in the implementation of environmental law, and analyse the efficaciousness of the existing dispute resolution mechanisms. To this end, it employs qualitative methods, with a particular focus on primary data obtained through observation, interviews, and documentation. The findings demonstrate that, despite an adequate legal framework, the efficacy of environmental dispute resolution is constrained by challenges inherent in law enforcement, public awareness, and economic considerations.